This action might not be possible to undo. Are you sure you want to continue?

# SSG 516 Mechanics of Continua

Lecture Two Kinematics: Study of Displacements & Motion “…the various possible types of motion in themselves, leaving out … the causes to which the initiation of motion may be ascribed … constitutes the science of Kinematics.”—ET Whittaker

Helpful Reading: Bower pp 13-27, Fakinlede 146-177

Kinematics

Kinematics is an organized geometrical description of displacement and motion. The emphasis here is the fact that displacement and motion are independent of the material constitution. While we may use the terminology of solid mechanics the concepts and the ensuing relationships are independent of the particular materials involved. We shall also define the concepts of strain and strain rates as deriving from displacements and motion.

**Simple Shear of a Cube
**

Our cube, for simplicity will have the dimension of unity and with one edge at the origin. Let 𝑥1 , 𝑦1 represent the initial Cartesian coordinates in an undeformed body. We consider the transformation, 𝑥2 1 𝑦 = 𝛽 2 0 1 𝑥1 𝑦1

1 1 0 0 1 0 0 1 → , → , → , → tan 𝛽 1 + tan 𝛽 0 0 0 1 1 1 And for small values of 𝛽, we can easily see that, 1 1 0 0 1 0 0 1 → , → , → , → 𝛽 1 + 𝛽 0 0 0 1 1 1

Horizontal Shear

Similar to the above, the transformation, 𝑥2 1 𝑦 = 2 0 𝛼 1 𝑥1 𝑦1

Transforms the edges as, 𝛼 0 0 1 1 0 1 1 + 𝛼 → , → , → , → 1 0 0 0 0 1 1 1 The square element in the above diagram has therefore undergone a shearing in the horizontal axes as shown.

Mathematica Code

General Deformation

We have seen how a simple tensor can be used to transform a simple shape into a new shape. We are now to generalise this concept using the figure (Bower) below:

Transformation equations

As a result of the transformation, 𝒙 → 𝒚 such that, 𝒚(𝒙, 𝑡) = 𝒙 + 𝒖(𝒙, 𝑡) Using the linear gradient operator we defined last term, we can take the gradient of the above equation and obtain, grad 𝒚(𝒙, 𝑡) = grad 𝒙 + 𝒖 𝒙, 𝑡 ≡ 𝑭(𝒙, 𝑡) = 𝑰 + grad𝒖 𝒙, 𝑡 [In component form,
𝜕𝑦𝑖

𝜕𝑥𝑗

= 𝜕𝑥𝑖

𝜕𝑥𝑗

+ 𝜕𝑢𝑖

𝜕𝑥𝑗

= 𝛿𝑖𝑗 + 𝜕𝑢𝑖

] 𝜕𝑥𝑗

Recall that by definition, 𝒚 𝒙 + 𝑑𝒙, 𝑡 − 𝒚 𝒙, 𝑡 = grad 𝒚 𝒙 + 𝑑𝒙, 𝑡 𝑑𝒙 + 𝒐( 𝒅𝒙 ) So that as 𝑑𝒙 → 𝒐 we can write that 𝑑𝒚 = 𝑭𝑑𝒙 Or in full in full component form, 𝑑𝑦𝑖 = 𝐹𝑖𝑗 𝑥𝑗

**The Deformation Gradient
**

The equation, 𝑑𝒚 = 𝑭𝑑𝒙 transforms an element 𝑑𝒙 in the original configuration to 𝑑𝒚. Note that while we have suppressed the dependency of the deformation gradient 𝑭 on the location and time, it is general a function of both. It is therefore more accurate to write, 𝑭 = 𝑭(𝒙, 𝑡) This tensor contains all the necessary information about the deformation. Once the deformation gradient is specified for all locations and time, we can always find the new configuration based on an initial state and a given time 𝑡.

**Inverse & Multiple Transformations
**

The mapping 𝑑𝒚 = 𝑭𝑑𝒙 is necessarily one to one because of the physical implications. It necessarily has an inverse. Therefore, given a new configuration, we can obtain the old configuration that resulted in it, as 𝑑𝒙 = 𝑭−𝟏 𝑑𝒚 Furthermore, for two successive deformation gradients, 𝑭𝟏 and 𝑭𝟐 , 𝑑𝒚 = 𝑭𝟏 𝑑𝒙, and 𝑑𝒛 = 𝑭𝟐 𝑑𝒚 we can easily see that, 2 1 𝑑𝒛 = 𝑭𝟐 𝑑𝒚 = 𝑭𝟐 𝑭𝟏 𝑑𝒙 or that 𝑑𝑧𝑖 = 𝐹𝑖𝑗 𝐹𝑗𝑘 𝑥𝑘

Transformation of a line element

**Volume as a triple product
**

Consider the simple parallelepiped shown here. The base area, A = 𝑏𝑐 sin 𝜃 is 𝐛 × 𝐜 or 𝐀 = 𝐛 × 𝐜 in index notation, this cross product is 𝐴𝑖 = 𝜖𝑖𝑗𝑘 𝑏𝑗 𝑐𝑘 the perpendicular height is 𝑎 cos 𝛼 so that the volume is 𝐀 ⋅ 𝐚 = A𝑎 cos 𝛼 = 𝐚 ⋅ 𝐛 × 𝐜 = 𝐴𝑖 𝑎𝑖 = 𝜖𝑖𝑗𝑘 𝑎𝑖 𝑏𝑗 𝑐𝑘

Jacobian

The Jacobian of F

Recall that in component form, 𝐹𝑖𝑗 = 𝛿𝑖𝑗 + 𝜕𝑥 𝑖 so that
𝑗
𝜕𝑢

**the Jacobian determinant of the deformation, 𝐽 = det 𝑭 = det(𝛿𝑖𝑗 +
𝜕𝑢𝑖**

𝜕𝑥𝑗

)

This is a measure of the change in volume as a result of the deformation. If the three sides of a parallelepiped deform as, 𝑑𝑢𝑖 = 𝐹𝑖𝛼 𝑑𝑥𝛼 , 𝑑𝑣𝑗 = 𝐹 𝑑𝑦𝛽 and 𝑑𝑤𝑘 = 𝐹𝑘𝛾 𝑑𝑧𝛾 , then 𝑗𝛽 𝑑𝑉0 = 𝜖𝛼𝛽𝛾 𝑑𝑥𝛼 𝑑𝑦𝛽 𝑑𝑧𝛾 and 𝑑𝑉 = 𝜖𝑖𝑗𝑘 𝑑𝑢𝑖 𝑑𝑣𝑗 𝑑𝑤𝑘

The Jacobian

Clearly, 𝑑𝑉 = 𝜖𝑖𝑗𝑘 𝑑𝑢𝑖 𝑑𝑣𝑗 𝑑𝑤𝑘 = 𝜖𝑖𝑗𝑘 𝐹𝑖𝛼 𝐹𝑗𝛽 𝐹𝑘𝛾 𝑑𝑥𝛼 𝑑𝑦𝛽 𝑑𝑧𝛾 = det 𝑭 𝜖𝛼𝛽𝛾 𝑑𝑥𝛼 𝑑𝑦𝛽 𝑑𝑧𝛾 = 𝐽𝑑𝑉0

So that,

[To understand the above expression, note that in two-D, det F = 𝜖𝑖𝑗 𝐹𝑖1 𝐹𝑗2 and that 𝜖𝑖𝑗 𝐹𝑖𝛼 𝐹𝑗𝛽 = 𝜖𝛼𝛽 det F. It is easy to work the 2-D version out manually so understand the 3-D] 𝑑𝑉

= 𝐽 𝑑𝑉0

Mass density

Furthermore, it is easily shown that mass density is related as 𝜌 =
𝜌

0 𝐽

This follows from the above derivation. Show this to be true.

**Lagrangian Strain Tensor
**

1 𝐅 = 𝐹 = 𝜖𝑖𝑗𝑘 𝜖𝑟𝑠𝑡 𝐹𝑖𝑟 𝐹𝑗𝑠 𝐹𝑘𝑡 3! Differentiating wrt 𝐹𝛼𝛽 , we obtain, 𝜕𝐹𝑗𝑠 𝜕𝐹 1 𝜕𝐹𝑖𝑟 𝜕𝐹𝑘𝑡 = 𝜖𝑖𝑗𝑘 𝜖𝑟𝑠𝑡 𝐹𝑗𝑠 𝐹𝑘𝑡 + 𝐹𝑖𝑟 𝐹𝑘𝑡 + 𝐹𝑖𝑟 𝐹𝑗𝑠 𝜕𝐹𝛼𝛽 3! 𝜕𝐹𝛼𝛽 𝜕𝐹𝛼𝛽 𝜕𝐹𝛼𝛽

1 𝜖𝑖𝑗𝑘 𝜖𝑟𝑠𝑡 𝛿𝑖𝛼 𝛿𝑟𝛽 𝐹𝑗𝑠 𝐹𝑘𝑡 + 𝐹𝑖𝑟 𝛿𝑗𝛼 𝛿𝑠𝛽 𝐹𝑘𝑡 + 𝐹𝑖𝑟 𝐹𝑗𝑠 𝛿𝑘𝛼 𝛿𝑡𝛽 3! 1 = 𝜖𝛼𝑗𝑘 𝜖𝛽𝑠𝑡 𝐹𝑗𝑠 𝐹𝑘𝑡 + 𝐹𝑗𝑠 𝐹𝑘𝑡 + 𝐹𝑗𝑠 𝐹𝑘𝑡 3! 1 𝐂 = 𝜖𝛼𝑗𝑘 𝜖𝛽𝑠𝑡 𝐹𝑗𝑠 𝐹𝑘𝑡 ≡ 𝐹𝛼𝛽 2! The cofactor of 𝑭 =

**The Right Cauchy-Green Tensor
**

The tensor 𝐂 ≡ 𝐅 T 𝐅 plays and important role in continuum mechanics. It is called the right CauchyGreen Tensor. The concept of strain is used to evaluate how much a given displacement differs locally from a rigid body displacement. Consequently, a strain function is a point function that vanishes in a state consisting of only rigid body displacements.

Strain Functions

We will introduce the two most common strain functions and demonstrate what they mean in one dimension: Lagrangian and Eulerian Strains.

First the Lagrangian Strain: 𝐄 = (𝐂 − 𝐈)

Notice that when there is no deformation, we can assume that the deformation gradient is the identity tensor (Why?). In this case, 𝐂 ≡ 𝐅 T 𝐅 = 𝐈. Clearly 𝐄 = 𝟎, the zero tensor.

1 2

First, show that

1 1 𝜕𝑢𝑖 𝜕𝑢𝑗 𝜕𝑢𝑘 𝜕𝑢𝑘 𝐸𝑖𝑗 = 𝐹𝑘𝑖 𝐹𝑘𝑗 − 𝛿𝑖𝑗 = + + 2 2 𝜕𝑥𝑗 𝜕𝑥𝑖 𝜕𝑥𝑗 𝜕𝑥𝑖

For example let 𝑖 = 1, 𝑗 = 1:

1 1 𝐹𝑘𝑖 𝐹𝑘𝑗 − 𝛿𝑖𝑗 = 𝐹11 𝐹11 + 𝐹21 𝐹21 + 𝐹31 𝐹31 − 𝛿11 2 2 1 𝜕𝑢1 𝜕𝑢1 𝜕𝑢2 𝜕𝑢2 𝜕𝑢3 𝜕𝑢3 = 𝛿11 + 𝛿11 + + + − 𝛿11 2 𝜕𝑥1 𝜕𝑥1 𝜕𝑥1 𝜕𝑥1 𝜕𝑥1 𝜕𝑥1 1 𝜕𝑢1 𝜕𝑢1 𝜕𝑢1 𝜕𝑢2 𝜕𝑢2 𝜕𝑢3 𝜕𝑢3 = 2 + + + 2 𝜕𝑥1 𝜕𝑥1 𝜕𝑥1 𝜕𝑥1 𝜕𝑥1 𝜕𝑥1 𝜕𝑥1

Eulerian Strain 𝑭

−1 = 𝑯 where 𝑭 is the deformation gradient tensor and 𝑯 is its inverse. If we take the coordinates 𝑥𝑘 , 𝑘 = 1, … , 3 as the material coordinates and 𝑦𝑙 , 𝑙 = 1, … , 3 as spatial coordinates, then simple chain rule implies, 𝜕𝑥𝑗

𝑑𝑥𝑗 = 𝑑𝑦𝑖 = 𝐻𝑗𝑖 𝑑𝑦𝑖 𝜕𝑦𝑖

Eulerian Strain

We can therefore write that,
𝑑𝑥𝑘

𝑑𝑥𝑘 = 𝐻𝑘𝑖 𝐻𝑘𝑗 𝑑𝑦𝑖 𝑑𝑦𝑗 If the unit vector along the deformed element 𝑑𝑦𝑖 is 𝑛𝑖 , then the length 𝑙 of the element is given by: 𝑑𝑦𝑖 = 𝑙𝑛𝑖 Similarly, in the undeformed system, we have: 𝑑𝑥𝑖 = 𝑙0 𝑚𝑖 with 𝑚𝑖 as the unit vector aligned with the material element 𝑑𝑥 𝑖 . In this case, we can write, 𝑑𝑥𝑘 𝑑𝑥𝑘 = 𝐻𝑘𝑖 𝐻𝑘𝑗 𝑑𝑦𝑖 𝑑𝑦𝑗

= 𝐻𝑘𝑖 𝐻𝑘𝑗 𝑛𝑖 𝑛𝑗 𝑙 = 𝑙0

2 2

Eulerian Strain

The strain,

2 𝑙2 − 𝑙0 1 𝑒𝐸 = = 2 𝛿𝑖𝑗 − 𝐻𝑘𝑖 𝐻𝑘𝑗 2 2𝑙 2𝑙
𝑛𝑖

𝑛𝑗 𝑙2 = 𝐧 ⋅ 𝐞 ⋅ 𝐧

1 (𝐈 2

where 𝒆 is the Eulerian strain tensor, − 𝐅 −𝐓 𝐅 −𝟏 ). In component form, following the same arguments it may similarly be proved that in one dimensional strain,

2 𝑙2 − 𝑙0 𝑒𝐿 = 2 = 𝐦 ⋅ 𝐄 ⋅ 𝐦 2𝑙0

Strain of a line element

**Again, beginning with unit vectors 𝑚𝑖 , 𝑛𝑘 , 𝑑𝑦𝑘 = 𝑙𝑛𝑘 and 𝑑𝑥𝑖 = 𝑙0 𝑚𝑖 . Recall that with the deformation gradient transformation,
𝑑𝑦𝑘**

= 𝐹𝑘𝑖 𝑑𝑥𝑘 = 𝑙0 𝐹𝑘𝑖 𝑚𝑖 squaring, we have that,

2 𝑙 2 = 𝑑𝑦𝑘 𝑑𝑦𝑘 = 𝑙0 𝐹𝑘𝑖 𝐹𝑘𝑗 𝑚𝑖 𝑚𝑗 from which we can see that 2 2 2 𝑙 2 − 𝑙0 = 𝑙0 𝐹𝑘𝑖 𝐹𝑘𝑗 𝑚𝑖 𝑚𝑗 − 𝛿𝑖𝑗 𝑙0 𝑚𝑖 𝑚𝑗

2 (𝑙2 −𝑙0 )

2 2𝑙0

=

1 2 𝐹𝑘𝑖

𝐹𝑘𝑗 − 𝛿𝑖𝑗 𝑚𝑖 𝑚𝑗 = 2 𝐦 ⋅ 𝐅 𝐓 𝐅 − 𝐈 ⋅ 𝐦 = 𝐦 ⋅ 𝐄 ⋅ 𝐦

1

Infinitesimal Strain

2 (𝑙 2 −𝑙0 ) 𝑙 + 𝑙0 (𝑙 − 𝑙0 ) 2𝑙0 (𝑙 − 𝑙0 ) (𝑙 − 𝑙0 ) = ≈ = 2 2 2 𝑙0 2𝑙0 2𝑙0 2𝑙0

Which is the elementary definition of strain. We can see from here that this definition is only approximately correct when strain is small and will not be a valid strain function if the difference between 𝑙 and 𝑙0 is appreciable. When that happens, we have a situation called geometric nonlinearity in the sense that a linear function no longer defines the strain-displacement relation

Infinitesimal Strain

Another way to arrive at this same conclusion is to note that for small strains, the second-order terms in the Lagrangian function

𝐸𝑖𝑗 = 𝐸𝑖𝑗 ≈

1 2
𝐹𝑘𝑖

𝐹𝑘𝑗 − 𝛿𝑖𝑗 =
𝜕𝑢𝑗

𝜕𝑥𝑖

1 𝜕𝑢𝑖 2 𝜕𝑥𝑗

+ 𝜕𝑢𝑗

𝜕𝑥𝑖

+ 𝜕𝑢𝑘

𝜕𝑢𝑘 𝜕𝑥𝑗 𝜕𝑥𝑖

Is small so that,

Both the Lagrangian as well as the Eulerian strain become indistinguishable from small strain.

1 𝜕𝑢𝑖 [ 2 𝜕𝑥𝑗

+

]≈ 𝑒𝑖𝑗